2012
DOI: 10.4012/dmj.2012-022
|View full text |Cite
|
Sign up to set email alerts
|

Morphological confocal laser scanning microscope evaluation of four different “etch and rinse^|^quot; adhesives in post endodontic restoration

Abstract: The aim of this study was to perform a morphometric evaluation of the resin-root canal dentine interface of four "etch and rinse" adhesive systems. Forty human teeth were restored through a fiber post insertion using: Group 1: XP Bond adhesive; Group 2: Prime & Bond NT; Group 3: Surgi Prime Bond adhesive; Group 4: Scotchbond Multi-Purpose Plus. Two cross-sections (apical and coronal) were obtained and analyzed in morphological confocal laser scanning microscope. The numbers of resin tags (RT) and the thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…Analysis of the micromechanical interaction of the adhesive interface was performed using confocal microscopy. This method evaluates the micropermeability and the sealing ability of the resin tags at the adhesive interface by using fluorescent dyes in the dental substrate and/ or resinous material [ 36 ], allowing for the evaluation of the subsurface. This is a non-destructive method which offers more details regarding the identification of the structures that constitute the adhesive interface [ 29 ] with less artefacts and decreased halo formation in the image when compared to scanning electronic microscopy [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the micromechanical interaction of the adhesive interface was performed using confocal microscopy. This method evaluates the micropermeability and the sealing ability of the resin tags at the adhesive interface by using fluorescent dyes in the dental substrate and/ or resinous material [ 36 ], allowing for the evaluation of the subsurface. This is a non-destructive method which offers more details regarding the identification of the structures that constitute the adhesive interface [ 29 ] with less artefacts and decreased halo formation in the image when compared to scanning electronic microscopy [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the use of Rhodamine B, this technique allows great precision in assessing the depth and number of tubules showing penetration, as well as the perimeter of the canal in which the marked material is located. Bitter et al in 2009 (18) and Marigo et al in 2012 (20) demonstrated that fluorochrome binding with the cements or adhesive-systems to which they are added does not modify the properties of the latter (20,21). With this examination process it is not necessary to subject the samples to any drying processes (as occurs with scanning electron microscopy, for example) that might result in material disadaptation or scaling.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the interface with dentin, the Prime & Bond 2.1/Self Cure + Enforce presented a uniform formation of tags with gaps ( Figure 6A). The confocal microscopy analysis also observed that the use of etch & rinse adhesive systems produced good results in terms of density and the quality of resin tags [13,15]. Polymerization shrinkage stresses that were generated because of the highly unfavorable cavity configuration factor of the post spaces may affect the interfacial strength of resin-based material, causing gaps in the adhesive interface ( Figure 6A) [4,16].…”
Section: Groups With Asterisks Statistically Differ From the Others mentioning
confidence: 97%
“…restored with adhesive materials, including the bonding process of glass fiber posts and resin cements to dentin [12,13]. However, different methodologies have been used according to the objectives of the study.…”
Section: Groups With Asterisks Statistically Differ From the Others mentioning
confidence: 99%